2016
DOI: 10.1002/ccd.26617
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy profile of bioresorbable‐polylactide‐polymer‐biolimus‐A9‐eluting stents versus durable‐polymer‐everolimus‐ and zotarolimus‐eluting stents in patients with acute coronary syndrome

Abstract: Long-term safety and efficacy of bioresorbable-polymer-BES and durable-polymer-EES/ZES appear comparable in patients with ACS. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…1,2) However, Japanese individuals exhibit weaker responses to clopidogrel, a classic P2Y12 receptor inhibitor, owing to an increased incidence of CYP2C19 loss-of-function polymorphisms.…”
mentioning
confidence: 99%
“…1,2) However, Japanese individuals exhibit weaker responses to clopidogrel, a classic P2Y12 receptor inhibitor, owing to an increased incidence of CYP2C19 loss-of-function polymorphisms.…”
mentioning
confidence: 99%
“…In a study consisting of 1899 patients, the rates were reported for TLR (3.0%), MI (2.4%), all-cause death (7.4%), and definite or probable stent thrombosis (1.6%) [ 13 ]. On the contrary, these very favorable results appeared to be worse than those found with thin-strut-durable-polymer-everolimus- and zotarolimus-eluting stents at 5 years in a study consisting of 1547 patients with very low TLR rate (2.0%), MI (5.3%), all-cause death (4.8%), and definite and probable stent thrombosis (2.1%) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in interventional techniques, and the improvement in DES design by decreasing strut thickness, using more biocompatible polymers, or reducing drug load have improved the outcomes of patients with acute coronary syndromes treated by PCI . Even if the current permanent DES are associated with a high clinical performance even in STEMI patients , all they have shortcomings related to the permanent caging of the coronary wall at the original “culprit” site.…”
Section: Discussionmentioning
confidence: 99%